Peran Penting Organisasi Advokat Dalam Membentuk Karakter Sesuai dengan Kode Etik Keadovokat di Indonesia - Raydatul Maqfirah; Fauziah Lubis; Chairany Kartika Sipayung, (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Advocates are one of the law enforcers in Indonesia, therefore, like other law enforcers in Indonesia, advocates in their formation must be based on special advocacy education which is usually held for 6 months. This was done because syraiah scholars and other law graduates were accepted as advocates, so this special advocacy education was held with the aim of equalizing learning related to advocacy to produce advocates who are in accordance with their functions and duties as advocates. Special education for the advocacy profession is organized by an advocacy organization where PERADI is the parent organization for advocates in Indonesia which was established based on a law so that it has the authority to organize this education. Furthermore, in carrying out special advocacy education, PERADI can partner with other agencies/institutions in the special advocacy education program with the condition that they must first obtain approval from PERADI which is shown through a letter of agreement. And after attending special advocacy education, you don't immediately become an advocate, prospective advocates must take an exam to become an advocate profession and be legalized and appointed as an advocate by an advocate organization which in Article 2 paragraph 2 of Law No. 18 of 2003 states that PERADI is the highest advocacy organization. and then the advocate takes the oath of office so that every advocate in Indonesia does not violate the advocacy code of ethics. In this case, it is explained in Article 30 paragraph 2 of Law No. 18 of 2003 that every prospective advocate who has been appointed as an advocate by an advocate organization based on the Advocate Law, is obliged to become a member of that advocate organization. In the case of this very long and strict examination related to candidates for the position of advocate, it is hoped that all those who will become advocates in Indonesia will not violate their oath of office and violate the advocacy code of ethics and will run according to their advocacy function, namely as advisors and law enforcers who are protected by law in Indonesia. Keywords: role, advocate organization, advocate profession